Short communication: In vitro oocyte maturation and fertilization rates in the Spanish Lidia bovine breed - Demyda-Peyrás, S.; Hidalgo, M.; Dorado, J.; Anter, J.; Género, E.; Moreno Millán, M. (Spanish Journal of Agricultural Research, 2013)
The Lidia bovine breed is the most successful cattle breed on the Iberian Peninsula, also considered a hallmark of Spanish tradition and image around the world. The aims of the study were to characterize the oocyte recovery rates and to evaluate the effect of two standard in vitro maturation protocols on oocyte maturation (cumulus expansion and nuclear maturation) and fertilization rates after in vitro fertilization in this breed. For this purpose, 261 ovaries from Lidia cows were processed obtaining 1,125 viable cumulus oocyte complexes (COCs). The oocyte recovery rate obtained (4.31 viable COCs per ovary) was lower than those described previously in other studied breeds. Maturation rates were evaluated in two different oocyte maturation media with (M1) and without (M2) hormonal supplementation. The percentage of COCs with expanded cumulus cells was significantly lower in M1 (74.35%) compared with M2 (82.25%). Metaphase II (MII) rates (67.75% in M1 and 73.18% in M2) were similar to previous studies in different cattle populations. M2 significantly improved the percentage of COCs with their cumulus cells expanded (p<0.01) and nuclear maturation rates (p<0.05), but it did not affect the fertilization percentages obtained in this experiment. In conclusion, our study suggests that oocytes of the Lidia cattle breed can be obtained, matured and fertilized following standard protocols previously used in other cattle breeds.